2016
DOI: 10.1155/2016/3564359
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasite Profile in the Stool of HIV Positive Patients in relation to Immune Status and Comparison of Various Diagnostic Techniques with Special Reference toCryptosporidiumat a Tertiary Care Hospital in South India

Abstract: Acquired immunodeficiency syndrome and related opportunistic infections are a significant cause of morbidity and mortality in susceptible population. This study aims to negate the paucity of data regarding the relation between CD4 levels, prevalence of enteric parasites, and the outcome of treatment with HAART (highly active antiretroviral therapy) and Cotrimoxazole in Kerala, India. Multiple stool samples from 200 patients in a cross-sectional study were subjected to microscopy and Cryptosporidium stool antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
6
3
Order By: Relevance
“…This prevalence was higher than in similar studies e.g. from Nigeria (5) or southern India (6), but lower than the prevalence described in previous studies from Ethiopia (i.e. from Desie (7), Butajira (8) and Bahir Dar (9)).…”
Section: Discussioncontrasting
confidence: 73%
“…This prevalence was higher than in similar studies e.g. from Nigeria (5) or southern India (6), but lower than the prevalence described in previous studies from Ethiopia (i.e. from Desie (7), Butajira (8) and Bahir Dar (9)).…”
Section: Discussioncontrasting
confidence: 73%
“…Another study of Rao RP et al 14 in 2015 from Mangalore, India reported 49% of parasitic infection in HIV seropositive patients. Kaniyarakkal V et al 22 from South India (Kozhikode) reported 9% as prevalence of parasitic infection which was very less as compared to this study. A study conducted by Swathirajan CR et al 23 from Tamil Nadu, India intestinal parasite infections are common among HIV/AIDS patients was 23.4% which showed similar with this study.…”
Section: Discussioncontrasting
confidence: 71%
“…Various researches from various parts of India also revealed a larger proportion of males in the HIV-infected population. This male preponderance may be related to men's proclivity to relocate for job, as well as their increased exposure to promiscuous and risky sex 22 . In this study the most common parasite was Taenia spp followed by Entamoeba histolytica, Cryptosporidium parvum was found in 23.8% of HIV seropositive patients.…”
Section: Discussionmentioning
confidence: 99%
“…was investigated in a population of HIV-positive adults and a prevalence of 3.92% (4/102) was found. Several studies have aimed to estimate the prevalence of cryptosporidiosis in immunocompromised populations in different countries [ 5 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]; however, the results are heterogeneous even with data collected within the same country [ 7 , 37 , 38 ]. The discrepancies between the studies could be attributed in part to their methodological design; however, all the components of the epidemiological triad, which includes the interaction between the host, the parasite and the environment, could be behind these inconsistencies.…”
Section: Discussionmentioning
confidence: 99%